Penanganan limbah industri dengan cara immobilisasi microbial cell - Prayitno, Prayitno (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1997)
An immobilized microbial cell is a physical confinement or localization of intact cell to a certain defined region of space with the preservation of some desired catalytic activity. The immobilization cell process has been increasingly used, one of those is for waste water treatment industry. Microbial entrapping process one of the method for the microbial cell immobilization by using some carrier such as collagen, gelatin, alginate, carragena and cellulose tri acetat at the time being is commonly used. Immobilization cell is effective enough for waste water treatment containing toxic substance such as phenol and by using immobilization cell, secondary sedimentation tanks is no longer used. INTISARI Immobilisasi mikrobia cell merupakan suatu cara untuk melokalisasi atau menahan secara physis cell lengkap pada tempat tertentu dengan memelihara aktivitas katalitik cell sesuai dengan yang diinginkan. Penggunaan immobilisasi cell saat ini terus meningkat, salah satunya adalah penggunaannya untuk pengolahan limbah cair industri. Proses immobilisasi cell dengan cara menjerat mikrobia dengan berbagai bahan pembaw seperti collagen, gelatin, agar alginate, carrogen, cellulose tri acetat saat ini merupakan metoda yang banyak digunakan. Metoda immobilisasi cell dapat memberikan efektifitas yang cukup tinggi untuk mengolah limbah cair yang mengandung bahan toksik seperti phemol dan tidak lagi diperlukan pengendap sekunder dalam proses pengolahan limbahnya.